Ristocetin - A New Tool in the Investigation of Platelet Aggregation - Howard, Margaret A.; Firkin, B. G (Thrombosis and Haemostasis, 1971)
1. The antibotic, Ristocetin, causes precipitation of fibrinogen from platelet poor plasma, as well as platelet aggregation.2. The precise mechanism of Ristocetin’s effect on platelets has not been elucidated, but it has been shown to initiate ADP release, which may contribute in part to its aggregating ability.3. Ristocetin has been shown to produce aggregation in platelet rich plasma from thrombasthenic patients.4. Three patients with Von Willebrand’s disease were examined. In 2, Ristocetin caused no platelet aggregation whatsoever, whilst the third aggregated normally. It is suggested, on this basis, that Von Willebrand’s disease may be subdivided into two types and that Ristocetin could prove to be a valuable technique for further study of this group of disorders.